Impact of Limit Feeding Finishing Beef Steers on Enteric Methane Production and Animal Performance - Carlee M. Salisbury; Jonn Albert Frey; Maria A. DeBernardi; Logan Thompson (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective of this experiment was to determine the impact of limit feeding on enteric methane (CH4) production and subsequent animal performance. Study Description: Angus-cross steers (n = 48, body weight [BW] = 985 ± 9.7 lb) were blocked by BW and assigned to one of three treatment groups for a 134-day finishing experiment. Treatments consisted of a 1) control (CON) where steers were fed ad libitum; 2) treatment 1 (TRT1) where steers were fed 96% of ad libitum; and 3) treatment 2 (TRT2) where steers were fed 92% of ad libitum. Once weekly, TRT1 and TRT2 were adjusted based on the CON steers average intakes from the previous week. The BW was measured monthly and dry matter intake (DMI; lb/day) was measured using an Insentec Roughage Intake Control System (Insentec, Markenesse, The Netherlands). Enteric methane and carbon dioxide (CO2) production was determined utilizing two GreenFeed emission measurement systems (AHCS; C-Lock Inc., Rapid City, SD). The Bottom Line: Limit feeding of finishing beef steers at 96% ad libitum resulted in a 17% reduction in enteric CH4 emissions. However, final BW tended to be lower at finishing for limit-fed steers. For the reduction in emissions to be economically advantageous, economic incentives for producers would be needed to offset this less desirable endpoint.
Keywords: finishing steers; enteric methane